Evaluation of Association of Oral Bacterial Profile with HBV and HCV Infection and T Lymphocyte Level in HIV-Positive Patients - Fatemeh Lavaee; Farzan Modarresi; Samira Amookhteh; Mohammad Amin Amiri (International Journal of Dentistry)
Background. This study was aimed to determine the oral bacterial profile of HIV-positive patients and their correlation with T lymphocyte and CD4 count and hepatitis B and C incidence. Methods. In this study, 73 patients who were diagnosed HIV-positive and were referred to Shiraz HIV research center for routine dental treatment were enrolled. Demographic data including sex, ethnicity, CD4+ T cell, and T lymphocyte counts were collected from their medical records. Supragingival dental plaque and samples from the dorsal of the tongue were collected by sterile swabs. These samples were transferred to the microbiology laboratory of Jahrom University of Medical Sciences. After primary biochemical test of cultured samples, assessment of bacterial biofilms was done by DNA extraction. Real-time PCR with specific primer of each bacterial species was done, and assessment of the results of real time PCR led to determination of the species of the evaluated bacteria. The correlation of bacterial prevalence with hepatitis B and C was evaluated by chi-square test. Furthermore, Mann–Whitney test was used to evaluate the association of bacterial species prevalence with CD4 and T lymphocyte level. Results. The prevalence of none of the detected bacteria had statistically significant relationship with hepatitis C, except for Peptostreptococcaceae (p value = 0.016) in the tongue plaque and Leptotrichia (p value = 0.022) in dental plaque. None of the evaluated bacteria showed any significant association with CD4 and T lymphocytes level, except for Kingella (p value = 0.025, 0.019, respectively), and also no significant correlation was reported with CD4, except for Gemella (p value = 0.021) and Campylobacter gracilis (p value = 0.029). Conclusions. The diversity of the detected bacteria was more in dental plaque, while their density was more noticeable in the tongue plaque. No significant correlation was found between the prevalence of most of the detected bacteria and CD4 level and T lymphocyte level and incidence of hepatitis B and C.